Novel small molecule protein kinase CK2 inhibitors exert potent antitumor effects on T98G and SEGA cells in vitro - Pucko, Emanuela; Ostrowski, Robert; Matyja, Ewa (Folia Neuropathologica, 2019)
Tumours of astroglial origin, both malignant glioblastoma (GBM) and benign subependymal giant cell astrocytoma (SEGA), pose a serious medical problem. Casein kinase 2 (CK2), a member of the serine/threonine kinase family, has antiapoptotic properties and plays a vital role in glial tumour cell survival. It contributes to invasive cell growth and is often upregulated in malignant neoplastic cells; however, its role in benign tumours of astrocytic origin is less understood. In the present study we investigated the effects of small molecule CK2 inhibitors on proliferation and viability of glioma cells in vitro. The experiments were conducted on commercial T98G malignant glioma cell line and the SEGA cell line, derived from a paediatric case of tuberous sclerosis complex (TSC). Cell cultures were incubated with selected CK2 inhibitors: 4,5,6,7-tetrabromo-1H-benzimidazole (TBI), 2-dimethylamino-4,5,6,7-tetrabromo-1H-benzimidazole (DMAT) and 4,5,6,7-tetrabromo-1H-benzotriazole (TBB) at 0.1, 1, 10, 25, 50, 75 and 100 µM concentrations for 24 and 48 hours. Cell proliferation was assessed using a cell counter and cell viability was evaluated by MTT assay. TBB at 75 µM and 100 µM, and TBI starting from 25 µM, both reduced T98G cell proliferation after 24 hours, while DMAT was ineffective. All tested small molecule CK2 inhibitors appear to reduce T98G cell growth and viability after 48 hours, although TBI appeared to be the most effective and reduced cell growth in the 50-100 µM dose range. TBI also showed potential efficacy in reducing the number and viability of SEGA cells after 48 hours. Proliferation and viability of SEGA cells have proven resistant to TBB treatment. DMAT only reduced the viability of SEGA cells at 24 (at 100 µM) and 48 hours (10-100 µM). Importantly, normal human astrocyte cells were found to be moderately resistant to TBB, while their viability was mildly reduced at higher doses of DMAT and TBI. In conclusion, CK2 appears to play a role not only in malignant glioma cells but it can also sustain the viability and proliferation of benign astrocytoma cells. The obtained antitumor effects of CK2 inhibitors significantly exceeded their mild or no effect on normal astrocytes in control, which supports the therapeutic potential of these compounds against gliomas.